Diversity of freshwater crab: new distributional data for four species (Decapoda: Pseudothelphusidae) from Meso- and South American countries - Magalhães, Célio (2025)
Introduction: The Pseudothelphusidae is a very diverse family of primary freshwater crabs widely distributed throughout the Neotropical region, but the true extent of the geographic distribution of several species is poorly known because many of them occur in very remote areas with only a single or very few records available. Objective: Here we present new country records for four species of pseudothelphusid crabs from Meso- and South American countries. Methods: The data about the geographic distribution are based on specimens deposited in crustacean collections of institutions from Brazil, Germany, and USA; illustrations of the male first gonopod were prepared in stereomicroscope equipped with a camera lucida. Results: Occurrence records of Phygiopilus acanthophallus Fredius stenolobus from Guyana, and Kunziana irengis from Brazil are published for the first time, and the occurrence of Raddaus mertensi from Honduras is confirmed. Comments on the morphology of the male first gonopod of each species are given, their range extensions are discussed, and the importance of these new records for conservation assessments is highlighted. Conclusions: The new data expand the area of occurrence of these four species of Pseudothelphusidae freshwater crabs, providing new data that are relevant for taxonomic and biogeographical studies as well as for the development of better regional and national assessments of the conservation status of the aquatic fauna.